A contemporary review of LGBTQ+ healthcare teaching in the UK medical curriculum. Issue 1 (1st December 2022) - Barber, Alice Tamar; Flach, Alexander James; Pattinson, Emily M
Abstract : Background: Changing societal views and the increasing prevalence of online education has created an environment ideal for the evolution and change of the medical curriculum. One area in need of improvement is LGBTQ+ health care teaching. Current literature demonstrates that LGBTQ+ individuals have higher levels of poor mental and physical health than heterosexual, cis-gender individuals (6). Therefore, it is key that the medical curriculum is made more inclusive of the LGBTQ+ population to ensure future doctors can provide inclusive care. This review aimed to examine the current literature on LGBTQ+ health care teaching in UK medical curricula, identify potential barriers to change, and explore efforts to improve the LGBTQ+ health care teaching in the UK. Methods: Literature searches were carried out using the PRISMA framework. The databases used were PubMed, Ovid, Embase, AMED, Global Health and Scopus. The searches were carried out in July 2021. Results: 15 relevant papers were reviewed. Three main themes were identified, 1) medical students (or medical schools) believed current education on LGBTQ+ health care was insufficient, 2) students reported wanting more in-depth practical education on LGBTQ+ health, 3) the potential impact of a lack of LGBTQ+ health care education on clinicians' confidence and ability to treat LGBTQ+ patients. Discussion: LGBTQ+ health care is lacking in the UK medical curriculum which has the potential to negatively impact patients. The teaching that is present is firstly inconsistent which leads to disparities and unreliability for LGBTQ+ patients. It is also heavily focused on sexual health which can lead to damaging stereotypes. Despite there being barriers to improving LGBTQ+ health care education, we present practical suggestions to overcome these. Further research should explore in greater depth the level of knowledge of medical students on LGBTQ+ health care, and their perceptions of curriculum improvements, in order to establish a basis for future curriculum change.